2018
DOI: 10.1186/s40545-018-0143-0
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of knowledge, attitudes and practices of hospital pharmacists towards adverse drug reaction reporting system in Lahore, Pakistan

Abstract: BackgroundMedication safety is a major public health concern and there are well established pharmacovigilance programmes in developed countries. However, there is scarcity of literature on the issue in low and middle income countries. In this context, the current study was aimed to evaluate the knowledge, attitudes and practices of hospital pharmacists towards medication safety and ADR reporting in Lahore, Pakistan.MethodsA qualitative approach was used to conduct this study. A semi-structured interview guide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 30 publications
2
31
1
Order By: Relevance
“…In the particular case of Bolivia, to our knowledge, this is the first time that a study of these characteristics has been performed. Similar studies have been carried out in other lower/middle income countries, where pharmacovigilance is still a relatively new concept [25][26][27]. All studies agree on the need for more research and literature, and for a stronger focus on the challenges and barriers to be overcome to promote and sustain pharmacovigilance in resourcelimited settings, prioritizing country's specific needs.…”
Section: Discussionsupporting
confidence: 58%
“…In the particular case of Bolivia, to our knowledge, this is the first time that a study of these characteristics has been performed. Similar studies have been carried out in other lower/middle income countries, where pharmacovigilance is still a relatively new concept [25][26][27]. All studies agree on the need for more research and literature, and for a stronger focus on the challenges and barriers to be overcome to promote and sustain pharmacovigilance in resourcelimited settings, prioritizing country's specific needs.…”
Section: Discussionsupporting
confidence: 58%
“…Accordingly, we found that the sociodemographic factors associated with more frequent practice measures were being female, older age, having higher education, higher income, urban area residence, and having more positive attitudes. Male gender, occupation of “students”, COVID-19 knowledge score, marital status, and residence were significantly associated factors in the Zhong et al study, while experience was indicated by Saqlain et al, Ivey et al and Hussain et al [ 31 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 89%
“…Participants who were registered physicians from Pakistan Medical and Dental Council and working as full-time permanent employees in a tertiary care hospital were recruited for the study. Participants in our study were purposively selected based on their convenience as per time and place availability with prior experience and an understanding of the health systems [22,23]. During recruitment, the selected participants were aware that participation for the interview was voluntary, and they were free to decline the participation.…”
Section: Study Sampling and Samplingmentioning
confidence: 99%